2003
DOI: 10.1124/jpet.102.041624
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Drug Idiosyncrasy—Is There a Connection?

Abstract: "Drug idiosyncrasy" refers to untoward reactions to drugs that occur in a small fraction of patients and have no obvious relationship to dose or duration of therapy. The liver is a frequent target for toxicity. Much of the conventional thinking about mechanisms of drug idiosyncrasy has centered on hypotheses that the reactions have a metabolic basis involving drug metabolism polymorphisms or that they arise from a specific immune response to the drug or its metabolite(s). For very few drugs does convincing evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 43 publications
1
63
0
1
Order By: Relevance
“…56 On the other hand, inflammatory stress might sensitize the liver to xenobiotics-induced injury. 57 Hence, we might be able to suggest that inflammatory stress occurring during antimalarial drug therapy might participate in antimalarial drugs-induced liver injury in patients and enhance the sensitivity to antimalarial drugs. Investigating the effect of inflammation on antimalarial drugs hepatotoxicity in a broader time frame will enhance our understanding of the mechanism of toxicity and the pathological pattern of liver injury induced by…”
Section: Discussionmentioning
confidence: 99%
“…56 On the other hand, inflammatory stress might sensitize the liver to xenobiotics-induced injury. 57 Hence, we might be able to suggest that inflammatory stress occurring during antimalarial drug therapy might participate in antimalarial drugs-induced liver injury in patients and enhance the sensitivity to antimalarial drugs. Investigating the effect of inflammation on antimalarial drugs hepatotoxicity in a broader time frame will enhance our understanding of the mechanism of toxicity and the pathological pattern of liver injury induced by…”
Section: Discussionmentioning
confidence: 99%
“…Roth found that cotreatment of animals with lipopolysaccaride (LPS) and drugs such as ranitidine causes immediate hepatic damage (42). He has proposed that we are commonly exposed to inflammagens such as LPS, and it is the combination of drug and inflammagen that leads to hepatic damage.…”
Section: Inflammagen Hypothesismentioning
confidence: 99%
“…Despite the lesser attention to the gut, an estimated 16,500 or more people die annually in the U.S. from complications associated with long term NSAID use (e.g., intestinal ulceration, bleeding, perforations, and strictures (Hirschowitz, 1994;Laney et al, 1994)), especially among elderly, arthritic patients (Wolfe et al, 1999). Moreover, an appreciated aspect of persistent low-level LPS exposure due to NSAID use is elevated risk of drug-induced idiosyncratic hepatic injuries (Roth et al, 2003), atherosclerosis (Blake and Ridker 2001;Shishehbor and Bhatt, 2004) and alcohol-induced hepatic injury (Mathurin et al, 2000;Schafer et al, 2002). To this point, pretreatment of rats with a mild APR inducing dose of LPS followed by a dose of ranitidine that in naïve animals is only mildly hepatotoxic synergistically increases hepatic injury (Luyendyk et al, 2003).…”
Section: Drug Signatures For the Acute Phase Responsementioning
confidence: 99%